2021
DOI: 10.3389/fpsyt.2021.666646
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Use of Subcutaneous Midazolam During an Episode of Catatonia

Abstract: Midazolam is a benzodiazepine (BZD) mainly used in anesthetic induction due to its pharmacokinetic features. Its place in the therapeutic management of catatonia remains to be determined. Here we present the case of a 65-year-old man who presented with a first episode of catatonia with opposition to any form of oral treatment, where a single dose of 1 mg of subcutaneous (SC) Midazolam permitted clinical improvement allowing oral treatment to be given. The patient's history notably included a renal transplant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Lorazepam is recommended as the first-line medication, and it is extensively reported to be highly effective, irrespective of the underlying cause[ 5 , 6 , 143 , 144 ]. Other BZDs, such as diazepam[ 128 , 145 ], midazolam[ 146 , 147 ], alprazolam[ 148 ], oxazepam[ 128 ], flunitrazepam[ 139 ], temazepam[ 128 ] and clorazepate[ 108 ], have also been described as useful in older people. This treatment should be maintained until the catatonia etiology is identified and appropriately treated[ 1 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lorazepam is recommended as the first-line medication, and it is extensively reported to be highly effective, irrespective of the underlying cause[ 5 , 6 , 143 , 144 ]. Other BZDs, such as diazepam[ 128 , 145 ], midazolam[ 146 , 147 ], alprazolam[ 148 ], oxazepam[ 128 ], flunitrazepam[ 139 ], temazepam[ 128 ] and clorazepate[ 108 ], have also been described as useful in older people. This treatment should be maintained until the catatonia etiology is identified and appropriately treated[ 1 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Catatonia: resolution IV or IM: 2-6 mg Maximum: 8-27 mg* per day 54,55 Case studies have demonstrated success of resolving catatonia, but further research is needed. [56][57][58] Lorazepam is the preferred drug to both resolve and confirm a diagnosis of catatonia, but success has been reported with use of diazepam, oxazepam, and clonazepam. 59 Catatonia: lorazepam challenge test IV: 2 mg 2 Case report demonstrates use of midazolam in confirmation of catatonia diagnosis.…”
Section: Additional Challenges With Covid-19mentioning
confidence: 99%
“…59 Catatonia: lorazepam challenge test IV: 2 mg 2 Case report demonstrates use of midazolam in confirmation of catatonia diagnosis. 56 Treatment of COVID-induced catatonia is not only jeopardized by the shortage of lorazepam, the first-line drug of choice 69 but also may be impacted by the limitations on midazolam administration. Using the lowest conversion rate of lorazepam to midazolam of 1:1.5, the daily dose needed to treat catatonia can range from 3 to 40.5 mg/d.…”
Section: Additional Challenges With Covid-19mentioning
confidence: 99%